(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This is a powerful tool for effectively cleaning and organizing text data. It can remove unnecessary markers and eliminate excessive gaps, format the text, and remove repetitive sentences. These tools can easily manage large amounts of text data. Marketing is very useful in various fields such as research and data analysis. Text cleaning software is a versatile tool that can be customized to personal preferences and requirements. It offers public use, customized filters, and functions for storing and sending cleaned and formatted text data in various formats. The user- friendly design and robust functionality of the Text Refinement Program simplifies the process of revising text and provides every user with an effortless experience. In addition, automating these programs saves users valuable time and ensures precision and clarity in their documents.